PENGARUH LAYANAN PURNA JUAL TERHADAP LOYALITAS PELANGGAN PADA CV. SUMBER BARU MOTOR PURRWODADI PURWOREJO (Prospect : Jurnal Manajemen dan Akuntansi, 2018)
This study aims to determine whether there is a positive and significant influence between after sales service on customer loyalty in CV. Purwodadi Purworejo Motor New Source. Analyzer used is with tool of SPSS 19,0 for windows. Taking samples done by Purposive Sampling, the number of samplestaken in this study is 16.7% x 300 = 50.1 or 50 people. The research method usedin collecting data is, simple regression, coefficient of determination, and t test.from the calculation of simple regression obtained regression equation Y = 14.280+ 0.265 X. the magnitude of coefficient of determination 0,108 or equal to 10.8%.This number means that as much as 10.8% customer loyalty that occurs can beexplained by using variable after-sales service. While the remaining 89.2% (100%-10.8%) received contributions from other causes factors such as promotions,recommendations from others, prices, deales locations. Hypothesis testing yielded tcount of 2,414. So the value of tcount is greater than this ttable means (Ha) which states there is a positive and significant influence between the variables after sales service to customer loyalist received and (Ho) rejected.